Desenvolvimento de um editor de lógica Fuzzy para o motor de jogo Unity - Feitosa, Francisco Diego Moreira (2019)
The development of digital games is a task that involves professionals from different areas and with different skills. Artificial Intelligence is a challenging aspect of game development, as it can involve a fair amount of code implementation and should provide the illusion of intelligent behavior for game agents. In other words, Artificial Intelligence is between design and programming (areas that do not always communicate in the most fluid way possible). In this context, this work details the design and implementation of the Fuzzy Logic Editor, a tool to aid the use of Fuzzy Logic in games. This tool allows the AI ​​designer to structure the variables and rules without the need for coding and, as far as we know, the first tool of this type totally free available for the Unity game engine. The preliminary assessment of the tool's usability indicates the success of its application in the development of a game prototype.